2011
DOI: 10.1111/j.1529-8817.2011.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE OF TRACHYDISCUS MINUTUS (XANTHOPHYCEAE) TO TEMPERATURE AND LIGHT1

Abstract: The effects of different temperatures and light intensities on growth, pigments, sugars, lipids, and proteins, as well as on some antioxidant and proteolytic enzymes of Trachydiscus minutus (Bourr.) H. Ettl, were investigated. The optimum growth temperature and light intensity were 25°C and 2 × 132 μmol photons · m(-2 ) · s(-1) , respectively. Under these conditions, proteins were the main biomass components (33.45% dry weight [dwt]), with high levels of carbohydrates (29% dwt) and lipids (21.77% dwt). T. minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Similar values were obtained by Gigova et al (2012) who studied the effect of temperature and light intensity on the same T. minutus strain. They reported that low temperature (about 15°C), which represents a stress condition for this microorganism, increased lipid accumulation to 35 %.…”
Section: Biomass Yield and Lipid Content Of Nzvi-treated Microalgaesupporting
confidence: 83%
See 1 more Smart Citation
“…Similar values were obtained by Gigova et al (2012) who studied the effect of temperature and light intensity on the same T. minutus strain. They reported that low temperature (about 15°C), which represents a stress condition for this microorganism, increased lipid accumulation to 35 %.…”
Section: Biomass Yield and Lipid Content Of Nzvi-treated Microalgaesupporting
confidence: 83%
“…They reported that low temperature (about 15°C), which represents a stress condition for this microorganism, increased lipid accumulation to 35 %. On the other hand, pronounced growth inhibition was found under these conditions (Gigova et al 2012).…”
Section: Biomass Yield and Lipid Content Of Nzvi-treated Microalgaementioning
confidence: 98%
“…In Scenedesmus obliquus, the final lipid store content varied between 18% and 40% of DW at temperatures between 20 o C and 27.5 o C. In general, storage starch and lipids are synthesized at all temperatures in the suboptimal range, but the final lipid or starch content is highest at the optimal temperatures favored for biomass growth (Breuer et al, 2013;Gigova et al, 2012;Roleda et al, 2013).…”
Section: Temperaturementioning
confidence: 98%
“…RuBisCO; see Nakamura and Miyachi 1982b). Although the detailed effect of temperature on carbohydrate content remains unclear, a few authors demonstrated a stimulation of carbohydrate synthesis when the temperature was increased to an optimal range (Oliveira et al 1999;Gigova et al 2012). On the other hand, Renaud et al (2002) reported a lack of relation between temperature and carbohydrate contents for Isochrysis sp., Rhodomonas sp., Cryptomonas sp., Chaetoceros sp., and Prymnesiophyte alga.…”
Section: Temperaturementioning
confidence: 99%